2011
DOI: 10.1242/dev.055566
|View full text |Cite
|
Sign up to set email alerts
|

Dishevelled-associated activator of morphogenesis 1 (Daam1) is required for heart morphogenesis

Abstract: SUMMARYDishevelled-associated activator of morphogenesis 1 (Daam1), a member of the formin protein family, plays an important role in regulating the actin cytoskeleton via mediation of linear actin assembly. Previous functional studies of Daam1 in lower species suggest its essential role in Drosophila trachea formation and Xenopus gastrulation. However, its in vivo physiological function in mammalian systems is largely unknown. We have generated Daam1-deficient mice via gene-trap technology and found that Daam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 41 publications
10
118
0
Order By: Relevance
“…Recent data using Daam1-knockout mice have established a crucial role in heart morphogenesis by regulating filamentous actin assembly and cytoskeletal organization. 38 The associated embryonic lethality precluded detailed analysis of the hematopoietic system, although DAAM1's megakaryocyte-enriched pattern of expression presumably connotes functional properties relevant to megakaryocytopoiesis and/or proplatelet formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data using Daam1-knockout mice have established a crucial role in heart morphogenesis by regulating filamentous actin assembly and cytoskeletal organization. 38 The associated embryonic lethality precluded detailed analysis of the hematopoietic system, although DAAM1's megakaryocyte-enriched pattern of expression presumably connotes functional properties relevant to megakaryocytopoiesis and/or proplatelet formation.…”
Section: Discussionmentioning
confidence: 99%
“…Formins also have essential roles in physiological processes ranging from cell motility in the immune system (Yayoshi-Yamamoto et al, 2000;Eisenmann et al, 2007;Shi et al, 2009), to gastrulation and neural tube closure (Habas et al, 2001;Sato et al, 2006;Lai et al, 2008), heart morphogenesis (Iskratsch et al, 2010;Li et al, 2011), kidney morphogenesis (Brown et al, 2010;Boyer et al, 2011a;Boyer et al, 2011b), and dendritic spine formation in neurons. Some of these functions depend on the actin nucleation and elongation activities of formins (Bartolini et al, 2008;Andrés-Delgado et al, 2010;Madrid et al, 2010;Andrés-Delgado et al, 2012;Ramabhadran et al, 2012;Stastna et al, 2012), which have been demonstrated by investigating point mutations that impair in these activities Lu et al, 2007;Ramabhadran et al, 2012).…”
Section: Cellular Functions Of Forminsmentioning
confidence: 99%
“…BrdU Staining and Terminal Deoxynucleotidyltransferasemediated dUTP Nick End Labeling (TUNEL) Assay-BrdU and TUNEL assays were performed as described previously (9). Briefly, mice were intraperitoneally injected with BrdU labeling reagent (30 mg/kg of body weight) and killed 3-4 h later.…”
Section: Mice-jupmentioning
confidence: 99%
“…Transmission Electron Microscopy-Transmission electron microscopy was performed as described previously (9). Skin samples were fixed in modified Karnovsky's fixative (2% paraformaldehyde and 2% glutaraldehyde in 0.1 M phosphate buffer) at 4°C overnight.…”
Section: Mice-jupmentioning
confidence: 99%